Relative Contribution of Blood Pressure in Childhood, Young- and Mid-Adulthood to Large Artery Stiffness in Mid-Adulthood - Meng Yaxing; Buscot Marie‐Jeanne; Juonala Markus; Wu Feitong; Armstrong Matthew K.; Fraser Brooklyn J.; Pahkala Katja; Hutri‐Kähönen Nina; Kähönen Mika; Laitinen Tomi; Viikari Jorma S. A.; Raitakari Olli T.; et al. (Wiley, 2022)
Background
Blood pressure associates with arterial stiffness, but the contribution of blood pressure at different life stages is unclear. We examined the relative contribution of childhood, young- and mid-adulthood blood pressure to mid-adulthood large artery stiffness.
Methods and Results
The sample comprised 1869 participants from the Cardiovascular Risk in Young Finns Study who had blood pressure measured in childhood (6-18 years), young-adulthood (21-30 years), and mid-adulthood (33-45 years). Markers of large artery stiffness were pulse wave velocity and carotid distensibility recorded in mid-adulthood. Bayesian relevant life course exposure models were used. For each 10-mm Hg higher cumulative systolic blood pressure across the life stages, pulse wave velocity was 0.56 m/s higher (95% credible interval: 0.49 to 0.63) and carotid distensibility was 0.13%/10 mm Hg lower (95% credible interval: -0.16 to -0.10). Of these total contributions, the highest contribution was attributed to mid-adulthood systolic blood pressure (relative weights: pulse wave velocity, childhood: 2.6%, young-adulthood: 5.4%, mid-adulthood: 92.0%; carotid distensibility, childhood: 5.6%; young-adulthood: 10.1%; mid-adulthood: 84.3%), with the greatest individual contribution coming from systolic blood pressure at the time point when pulse wave velocity and carotid distensibility were measured. The results were consistent for diastolic blood pressure, mean arterial pressure, and pulse pressure.
Conclusions
Although mid-adulthood blood pressure contributed most to mid-adulthood large artery stiffness, we observed small contributions from childhood and young-adulthood blood pressure. These findings suggest that the burden posed by arterial stiffness might be reduced by maintaining normal blood pressure levels at each life stage, with mid-adulthood a critical period for controlling blood pressure.